The heterogeneous relationship between income and inequality: a panel co-integration approach - Svenja Flechtner; Claudius Gräbner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
We study the relationship between per-capita income and income inequality with a heterogeneous panel co-integration approach. We extend previous studies in two dimensions: first, we compile a more extensive data set for 61 countries over 26-51 years and consider measures for both pre-tax and post-tax income inequality; second, we take into account country heterogeneity rather than relying on average panel estimates alone. We find a negative group-mean based relationship using pre-tax income inequality, but no such relationship for post-tax income inequality. Moreover, we find estimates on the country level to be heterogeneous in both cases.
Keywords: 330; Development; Inequality; Growth; Panel co-integration